Effect of Ni-modified reduced graphene oxide on the mechanical properties of Sn–58Bi solder joints. (May 2023) - Qin, Weiou; Yang, Wenchao; Zhang, Lei; Qi, Da; Song, Qianqian; Zhan, Yongzhong
Abstract: Sn–58Bi solder has great research value as a low-temperature solder. However, it still requires strengthening due to a lot of brittle Bi-phase, which reduces mechanical reliability. In this study, Ni-modified reduced graphene oxide (rGO@Ni) was prepared by heat reduction, and mechanical stirring was used to manufacture rGO@Ni-reinforced Sn–58Bi composite solder. The distribution, phase composition, and structural changes of graphene and Ni nanoparticles during enhancer synthesis were characterized in detail by Scanning Electron Microscope, Energy Dispersive Spectroscopy Raman and Fourier Transform Infrared spectra, X-ray Photoelectron Spectroscopy, X-ray Diffraction, and Transmission Electron Microscope. Besides, the morphology of intermetallic compound (IMC) layers of the composite solder/Cu interface was investigated. The thickness of the IMC layer decreases with the increase of rGO@Ni content. The microstructure analysis demonstrated that the rGO@Ni distributed near the IMC layer, which limits the diffusion of metal atoms and decreases the IMC layer's growth rate during the reflowing process. Besides, compared with Sn–58Bi solder alloys, the addition of 0.01 wt% rGO@Ni can increase the shear strength by up to 15%. However, when the content of rGO@Ni is more than 0.05 wt%, it agglomerates inside the composite solder, resulting in a decrease in the shear strength of the composite solder joint. Highlights: The Ni-modified rGO was prepared using sodium hypophosphate as a reducing agent. The Ni-modified rGO prevented the growth of Sn–58Bi/Cu intermetallic compounds. The Ni-modified rGO enhanced the shear properties of Sn–58Bi solder joints.